Oxidant–antioxidant Status and Lipid Profile in the Hypertensive Patients. - Maharjan, Babu Raja; Jha, J C; Vishwanath, P; Alurkar, V M; Singh, P P (Journal of Nepal Health Research Council, 2009)
Background: Hypertension is associated with an elevation of ROS and frequently also with an impairment of endogenous antioxidant mechanisms. Increased level of serum cholesterol, TG, VLDL has been observed in patients with hypertension. It has been shown that oxidized lipoprotein inactivates NO and aggravates hypertension. This study intends to know the association of oxidative stress and lipid profile with hypertensive patients of the Western Nepal. Methods: Our study group comprised of 32 confirmed cases of HTN. Inclusion criteria included the patients with blood pressure ≥140/90mm of Hg. Patients with secondary hypertension, past history of stroke, coronary artery disease (CAD), myocardial infarction, and peripheral vascular disease and diabetes mellitus were excluded. Serum lipid profile, plasma thiobarbituric acid reactive substances (PTBARS), plasma total antioxidant activity (TAA) and urinary thiobarbituric acid reactive substances (UTBARS) were estimated in these patients by standard procedures and the values were compared with 30 age, sex and socioeconomically matched normal healthy control subjects. Results: TBARS levels and Lipid profile were significantly raised in HTN patients, but TAA and urinary TBARS levels were comparable to normal subjects. BMI and W/H ratio in patients were comparable to control. Smoking and alcohol did not influence lipid profile, TBARS and TAA. Conclusion: Lipid profile and TBARS were significantly raised in HTN patients compare to controls. Thus, monitoring lipid level and maintaining oxidative balance in hypertensive patients would be helpful in preventing the diseases associated with hypertension. Key words: Hypertension; Lipid profile; Oxidative stress; Antioxidant; Nepal. doi: doi: 10.3126/jnhrc.v6i2.2185 Journal of Nepal Health Research Council Vol. 6, No. 2, 2008 October Page : 63-68